The Relationship between Quality of Working Life and Work-family Conflict among Nurses of Tehran University of Medical Sciences\' Hospitals - Amir Ashkan Nasiripour; Mehrak Pourmotahari (Tehran University of Medical Sciences, 2015)
Background: Nowadays, quality of working life as a universal concept of human resource management and organizational development have been regarded and improving it, is key to successfully managing any organization. This study was conducted to survey   Relationship between Quality of working life and Work-family conflict among Nurses of Hospitals in Tehran. Materials and Methods: This study is descriptive -analytic that performed cross sectional. The study population was the nurses of the hospitals of the Tehran University of Medical  sciences (N=215).The data was gathered using two questionnaires , Quality  of working life components of Casio and questionnaire of work-family conflict prepared based on Carlson. Cronbach's alpha was used to assess the reliability of the questionnaire. Spearman correlation test was used for statistical analysis. Results: There was no significant relationship between Education and work facilities (Quality of  working  life components) with the work-family conflict (p >0.05).but  relationship between the democracy, participation in decision making, job design, workplace in organization with the work-family conflict was significant (p <0.05).finally,  between Quality of  working  life  and  work-family conflict a significant relationship was observed (p <0.001). Conclusion: Because the significant relationship was observed between the Quality of working life and work-family conflict among the nurses, It can be concluded that Work-family conflict be reduced with improve of Quality of working life.